A Study of Corrosion Inhibitor Performance on Coating Pinhole Defects - Wan Alim, Wan Muhamad Izzat (2018)
In oil and gas industry, internal corrosion of pipeline is one of the major threats. Internal coating is one of the corrosion prevention methods for internal corrosion. However, the presence of pinhole on coating causes concern of localized corrosion. The objective of the project is to evaluate corrosion inhibitor efficiency and to study inhibition protective film formation on pinhole defects. The corrosion rate from weight loss immersion test and linear polarization resistance test will be calculated. After that, the corrosion inhibitor efficiency will be calculated based on the corrosion rate obtained. The result show that the presence of corrosion inhibitor decreases the corrosion rate of the coating pinhole defects from 0.1328 mm/year to 0.1056 mm/year for 25 ppm and 0.0709 mm/year for 50 ppm. The efficiency of the corrosion inhibitor is 20.48% for 25 ppm and 46.61% for 50 ppm. Therefore, the optimum concentration of corrosion inhibitor is at 50 ppm.